2014
DOI: 10.18632/oncotarget.3062
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of human papilloma virus on survival of basaloid squamous carcinoma of the head and neck

Abstract: ObjectivesBasaloid-squamous-carcinomas (BSCC) have been considered as aggressive variants of common squamous-cell-carcinomas (HNSCC). Recent studies demonstrated a different clinical course depending on the tumour site. The aim of the study is to analyze the histopathologic/clinical features of BSCC/HNSCC resolved by the HPV-status.MethodsWe analysed the histopathologic/clinical features of BSCC (n=59) and HNSCC (n=981), subdivided due to the HPV status. Differences were analysed using Chi square, Fisher exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…For instance HPV could inactivate the p53 tumor suppressor gene years before tumors occur and may be undetectable at the later stages. However, HPV DNA is usually detectable in tumors where it is thought to play a role in oncogenesis [ 20 ]. Also the fact that we detected no HPV DNA in early and advanced tumor stages argue against a role of HPV in early carcinogenesis and subsequently disappearing virus.…”
Section: Discussionmentioning
confidence: 99%
“…For instance HPV could inactivate the p53 tumor suppressor gene years before tumors occur and may be undetectable at the later stages. However, HPV DNA is usually detectable in tumors where it is thought to play a role in oncogenesis [ 20 ]. Also the fact that we detected no HPV DNA in early and advanced tumor stages argue against a role of HPV in early carcinogenesis and subsequently disappearing virus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ineffective radio-and chemotherapy comes at a high cost of significant patient morbidity without significant tumor regression. There have been implications for differences in response rates between HPV-negative and HPVassociated head and neck cancers; however, these indicators have not yet led to a change in therapy guidelines (14)(15)(16)(17). Recent ground-breaking studies have identified a large variety of inter-individual and intra-individual heterogeneity as a key reason for treatment resistance (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…An oncogenic HPV status has been described in 14/19 (73.7 %) cases of oropharyngeal SCNEC (Watson et al 2013 ; Kraft et al 2012 ; Bishop and Westra 2011 ). HPV infection confers a better prognosis for patients with oropharyngeal SqCC and basaloid SqCC (Gillison et al 2000 ; Jacobi et al 2015 ). However, the prognosis of patients with SCNEC of the oropharynx is poor, as the majority of patients die of the disease mainly due to systemic metastasis (Renner 2007 ; Wang et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%